PERDAGANGAN LINTAS BATAS ANTAR-NEGARA: MEMACU PEMBANGUNAN EKONOMI KABUPATEN BENGKAYANG DAN KABUPATEN BELU - Humphrey Wangke (Sekretariat Jenderal DPR RI, 2013)
The analysis in this essay refers to coordinated border management theory which emphasizes coordination inter- institutions, both vertically and horizontally, as well as inter-states, therefore, cross-border trade can be managed effectively. Indonesia which wants to create its border areas as its front yard is founded difficult to realize its dream due to the poor coordination among state institutions. This is contradictory with the potential conditions of its border areas such as in Bengkayang in West Kalimantan and Belu in East Nusa Tenggara, which respectively located close to Malaysia and Timor Leste. In fact, the formation of National Board for Border Management (BNPP) cannot automatically help overcome problems encountered in the many places of the country’s border. The essays is intended to give recommendations to DPR which is now discussing Bill on the Acceleration of Development in Underdeveloped Regions.